دور الأوعية الالكترونية في تحسين الوظائف الادارية لدى موظفي معهد علوم وتقنيات النشاطات البدنية والرياضية - عماري محجوية عزيزة; هواري بوشهير (My University, 2022)
عنوان الدراسة : دور الأوعية الالكتًونية في برستُ الوظائف الادارية لدى موظفي معهد علو وتقنيات النشاطات البدنية والرياضية . هدف الدراسة: معرفة دور الأوعية الالكتًونية في برستُ الوظائف الادارية لدى موظفي معهد علو وتقنيات النشاطات البدنية والرياضية . إشكالية الدراسة: ىل يوجد دور الأوعية الالكتًونية في برستُ الوظائف الادارية لدى موظفي معهد علو وتقنيات النشاطات البدنية والرياضية ؟ فرضيات الدراسة : - للؤوعية الالكتًونية دور في برستُ وظيفة التخطيط لدى موظفي معهد علو وتقنيات النشاطات البدنية والرياضية؟ - يوجد دور للؤوعية الالكتًونية في برستُ وظيفة الرقابة لدى موظفي معهد علو وتقنيات النشاطات البدنية والرياضية؟ - للؤوعية الالكتًونية دور في برستُ وظيفة التنظيم لدى موظفي معهد علو وتقنيات النشاطات البدنية والرياضية؟ - يوجد دور للؤوعية الالكتًونية في برستُ التوجيو لدى موظفي معهد علو وتقنيات النشاطات البدنية والرياضية ؟ - للؤوعية الالكتًونية دور في برستُ وظيفة التسيتَ لدى موظفي معهد علو وتقنيات النشاطات البدنية والرياضية؟ لا توجد فروؽ دالة إحصائيا في درجات تأثتَ الأوعية الالكتًونية على برستُ الوظائف الادارية تعزى بؼتلتَ ابعنس ؟ - المنهج المتبع في الدراسة : ابؼنهج الوصفي الأدوات المستخدمة في الدراسة : استبياف بغساب دور الأوعية الالكتًونية في برستُ الوظائف الادارية من اعداد الأستاذ ابؼشرؼ والطالبة الأساليب الإحصائية : * اختبار)ت( T.Test * معامل الارتباط بتَسوف r ) معامل الثبات ( * اختبار كاي 2 النتائج المتوصل إليها : برققت بصيع الفرضيات الاستنتاجات والاقتراحات : من خلبؿ نتائج الدراسة توصلت الباحثة إلى أف الأوعية الالكتًونية بؽا دور كبتَ في برستُ الوظائف الادارية لدى موظفي معهد علو وتقنيات النشاطات البدنية والرياضية .
)دراسة حالة معهد الأغىاط نمىذجا(
Study title: The role of electronic vessels in improving the administrative functions of the employees of the Institute of Science and Techniques of Physical and Sports Activities The aim of the study: To know the role of électronique vessels in improving the administrative functions of the employees of the Institute of Science and Techniques of Physical and Sports Activities The problem of the study: Is there a role for electronic vessels in improving the administrative functions of the employees of the Institute of Science and Technology of Physical and Sports Activities? Study hypotheses:  Electronic vessels have a role in improving the planning function of the employees of the Institute of Science and Technology of Physical and Sports Activities?  Is there a role for electronic vessels in improving the oversight function of the employees of the Institute of Science and Technology of Physical and Sports Activities?  Do electronic vessels have a role in improving the organizational function of the employees of the Institute of Science and Technology of Physical and Sports Activities?  Is there a role for electronic vessels in improving guidance among the employees of the Institute of Science and Technology of Physical and Sports Activities?  Do electronic vessels have a role in improving the management function of the employees of the Institute of Science and Technology of Physical and Sports Activities?  There are no statistically significant differences in the degrees of the effect of electronic vessels on improving administrative functions due to the gender variable? The method used in the study: the descriptive method Tools used in the study: A questionnaire to calculate the role of electronic vessels in improving administrative functions, prepared by the supervising professor and the student Statistical methods: * T.Test * Pearson correlation coefficient r (reliability coefficient) * Chi test 2 Results: All hypotheses were verified Conclusions and Suggestions: Through the results of the study, the researcher concluded that electronic vessels have a significant role in improving the administrative functions of the employees of the Institute of Science and Techniques of Physical and Sports Activities.